Analisis Yuridis Unsur “Tanpa Persetujuan” Terhadap Kepastian Hukum dalam UU TPKS: Penelitian - Putu Adinda Aneira Adnyana Putri; Dewa Bagus Sanjaya (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Sexual violence constitutes a serious violation of human rights that demands comprehensive and equitable legal protection. Law Number 12 of 2022 concerning the Crime of Sexual Violence (UU TPKS) marks significant progress by adopting the principle of “without consent” as an element of the offense. However, the absence of a clear normative definition and legal indicators for this term creates the potential for vague norms, thereby undermining the principles of lex certa and legality within criminal law. This study aims to analyze the juridical interpretation of the “without consent” element and to formulate an ideal legal framework to ensure legal certainty. The research employs a normative juridical method with statutory, conceptual, and case study approaches, focusing on two court decisions: Bantul District Court Decision No. 126/Pid.Sus/2023/PN Btl and Pandeglang District Court Decision No. 71/Pid.Sus/2023/PN Pdl. The findings indicate that the lack of a normative definition of “without consent” results in inconsistencies in judicial practice and difficulties in proving the element of the offense. Therefore, an explicit and operational legal formulation is required to ensure that the implementation of the UU TPKS upholds the principles of legal certainty and provides balanced protection for both victims and perpetrators.